The Swedish CArdioPulmonary BioImage Study: objectives and design. (19th June 2015) - Bergström, G.; Berglund, G.; Blomberg, A.; Brandberg, J.; Engström, G.; Engvall, J.; Eriksson, M.; de Faire, U.; Flinck, A.; Hansson, M. G.; Hedblad, B.; Hjelmgren, O.; et al.
Abstract: Cardiopulmonary diseases are major causes of death worldwide, but currently recommended strategies for diagnosis and prevention may be outdated because of recent changes in risk factor patterns. The Swedish CArdioPulmonarybioImage Study (SCAPIS) combines the use of new imaging technologies, advances in large‐scale 'omics' and epidemiological analyses to extensively characterize a Swedish cohort of 30 000 men and women aged between 50 and 64 years. The information obtained will be used to improve risk prediction of cardiopulmonary diseases and optimize the ability to study disease mechanisms. A comprehensive pilot study in 1111 individuals, which was completed in 2012, demonstrated the feasibility and financial and ethical consequences of SCAPIS. Recruitment to the national, multicentre study has recently started.